The impact of organizational climate on commitment and its influence on people turnover - Romana, Fernando Acabado; Gestoso, Carlos Guillen (Edelweiss Applied Science and Technology, 2025)
Organizational climate affects employee commitment and thus influences turnover. Because the environment of organizations is adaptable to various factors, including the social context and its norms, we identified relationships between commitment and leadership within the organization. The objective of the study was to understand the organizational environment and its influence on employee satisfaction and to verify whether there is a positive correlation between commitment and turnover. A quantitative approach was used; a questionnaire was applied to 85 individuals, aged 16–90, with market experience in Portugal, of which 49.4% were male and 50.6% were female. The results did not corroborate the expected correlation. Commitment decreases with an increase in the intention to leave due to employee dissatisfaction and lack of motivation, which then leads to an increase in turnover. It is necessary to improve communication and leadership to enhance the organizational climate and increase employee commitment, thus reducing turnover.